The effectiveness of digital twin in reducing downtime in the manufacturing industry: A literature analysis - S, Pipiet Mutiara Tri.; Nurraihan, Faiq (Trigin Publisher, 2025)
The Digital Twin is an innovative technology that significantly enhances operational efficiency and production in the industrial sector. This research seeks to examine the role of Digital Twin in mitigating both scheduled and unscheduled downtime, along with the technical and non-technical elements that affect its implementation efficacy. Literature review revealed that Digital Twin facilitates real-time monitoring, precise data analysis, and enhanced process modelling, all of which aid in minimising downtime. Moreover, elements such as system integration, data quality, organisational culture, and managerial support are essential for the successful application of this technology. The research findings indicate that appropriate investment in technological infrastructure and the formulation of management strategies that foster innovation enable organisations to optimise the advantages of Digital Twin. Companies are advised to enhance employee engagement and cultivate a collaborative work environment to attain sustained competitive advantage in the context of Industry 4.0.